Private Settlement - Public Justice? - Mahoney, P D (Victoria University of Wellington Law Review, 2000)
In this paper, the Principal Family Court Judge discusses the pros and cons of "court-annexed" mediation services. He notes some powerful constitutional arguments against such forms of mediation but eventually agrees with the stand taken by the Australian and New Zealand Council of Chief Justices in support of a fully serviced court-based system. This paper was delivered at the New Zealand Institute for Dispute Resolution Colloquium held on 29 June 1999.